A sample average approximation approach to the berth allocation problem with uncertain tides. Issue 10 (3rd October 2018) - Sheikholeslami, Abdorreza; Ilati, Reza
ABSTRACT: The remarkable increases in containerized trade over the past few years have resulted in increased congestion and operational costs of container terminals, indicating the importance of the effective management of port resources under uncertainty. In this article, a novel berth allocation model is suggested for seaports, taking into consideration the disruptive effects of tides on the berthing schedule as well as the uncertainty in the arrival time of vessels. A rigorous mathematical model is presented along with a sample average approximation method to generate an efficient berth allocation plan. In addition, statistical analysis of real data gathered from a real case is presented. Numerical analysis has been conducted to verify the practical applications of the model proposed for the berth allocation problem under uncertainty. Computational results based on a real-world data set provided by Rajaee port, Iran, demonstrate the effectiveness of the proposed solution method.